PERFORMANCE AND FACILITIES EVALUATION AT SURABAYA KOTA TRAIN STATION - Jane Prasasti; Amrita Winaya; Tigo Mindiastiwi (Department of Civil Engineering, Faculty of Engineering, Universitas Islam Malang, 2024)
Surabaya Kota Station continues to have several facility and service-related issues, thus some improvements must be taken to assess the level of service and station amenities by the Minimum Service Standards mandated by PM 48 of 2015. The purpose of this study, which employs the IPA (Importance Performance Analysis) approach, is to assess and contrast the level of service provided at Surabaya City Station with users' expectations for that level of service. Surabaya Kota Station's facilities have not met the minimum service requirements outlined in PM.48 of 2015, including platforms that are longer than 20 cm, a lack of space for nursing mothers, and a lack of accessible restrooms for the disabled. Customers are also dissatisfied with Surabaya Kota Station's facilities and services, which include the station building's untidy and dirty condition as well as the messy motorbike parking space. However, the station's service is fairly decent. The main contribution of this study is to identify significant gaps between user expectations and the reality of existing facilities, where facilities such as platforms, nursing mother rooms, and disability accessibility toilets require immediate attention. The results show that the cleanliness and management of parking spaces also greatly affect user satisfaction levels, and improvements in these areas are urgently needed to meet the service standards mandated by government regulations. Keywords: Importance Performance Analysis; Railway Infrastructure; Train Station Facilities.